Does gender moderate effects of religion on anxiety among Orthodox and non-Orthodox Jews? - Cherniak, Aaron D. (Mental health, religion & culture, 2021)
Studies examining religion's effects on mental health have insufficiently focused on basic moderators of observed effects. Given that Orthodox Jewish religious culture places greater ritual obligations on men than women, but is gender-equivalent regarding faith, we expected Orthodox Jewish men and women to experience different levels of anxiety in relation to religious practice but not intrinsic religiosity, and that no gender differences would exist among non-Orthodox Jews. In a community sample of 414 Jewish adults (51% Orthodox), religious practice differed predictably based on denomination and gender norms, and intrinsic religiosity was higher for Orthodox Jews. Both practice and intrinsic religiosity were associated with less anxiety overall. However, contrary to expectations, there were no interactions with gender. These results suggest that the effects of Jewish religious observance and belief on anxiety may not be gender-specific, even within communities that ascribe to more traditional religious values and gender roles.